(untitled) (Revista de História da UEG (REVHIST), 2021)
In this article, I intend to understand Friedrich Meinecke’s (1862-1954) position in the so-called crisis of historicism that took place in part of German historical tradition during the interwar period. In order to do so, I seek to reconstruct some of those intellectual quarrels by taking into account the relevance that the problems of historicism started to acquire in Meinecke’s work during the 1920s and the 1930s. Then, with an analysis of Meinecke’s own definition of the concept, I claim that the author of Die Entstehung des Historismus (The Emergence of Historicism) (1936) used J.W. Goethe’s philosophy of nature not only to define what he believed to be the climax of German historicism, but also to overcome what he conceived as the limits of the modern tradition of historical thought, as well as the boundaries of Western Enlightenment’s own conception of history. Finally, I argue that such a reinterpretation of Goethean naturalism – with its emphasis on the aesthetic ideal of the creative mirror – represented Meinecke’s own solution to the dilemmas of historicism and his own theoretical answer to the crisis discussed by part of German historical thought during the Weimar era and during the first years of the National Socialist dictatorship. Keywords: Friedrich Meinecke. J.W. Goethe. Historicism.